2022
DOI: 10.3389/fphar.2022.1067652
|View full text |Cite
|
Sign up to set email alerts
|

Progress of potential drugs targeted in lipid metabolism research

Abstract: Lipids are a class of complex hydrophobic molecules derived from fatty acids that not only form the structural basis of biological membranes but also regulate metabolism and maintain energy balance. The role of lipids in obesity and other metabolic diseases has recently received much attention, making lipid metabolism one of the attractive research areas. Several metabolic diseases are linked to lipid metabolism, including diabetes, obesity, and atherosclerosis. Additionally, lipid metabolism contributes to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 204 publications
0
4
0
Order By: Relevance
“…The compound disrupts citrate binding and recognition by inducing conformational changes in the citrate domain. This allosteric inhibition underscores the potential of the allosteric site as a promising target in drug discovery, enhancing the likelihood of ACLY inhibitors (Jha et al, 2021;K. Liang & Dai, 2022;P.…”
Section: Ndi-091143mentioning
confidence: 83%
“…The compound disrupts citrate binding and recognition by inducing conformational changes in the citrate domain. This allosteric inhibition underscores the potential of the allosteric site as a promising target in drug discovery, enhancing the likelihood of ACLY inhibitors (Jha et al, 2021;K. Liang & Dai, 2022;P.…”
Section: Ndi-091143mentioning
confidence: 83%
“…Recently, there has been a growing interest in targeting key players in lipid metabolism as potential therapeutic approaches for managing lipid metabolism in disease. [ 64 ] It is to note that conventional drug effects typically do not exhibit tissue specificity and lack a circadian perspective. Therefore, future developments of drugs regulating lipid metabolism with consideration of targeted tissue and circadian elements (such as optimal timing for meals and daily oscillation of lipid metabolism activities) might enhance efficacy, ensure safety, or mitigate potential side effects of a drug.…”
Section: Conclusion Significances and Future Directionsmentioning
confidence: 99%
“…Although aerobic glycolysis is less efficient in producing ATP compared to oxidative phosphorylation, it generates other metabolites that support tumor growth (Ashrafian, 2006). Lipid supply is crucial for the proliferation and survival of various cancer cells (Liang and Dai, 2022), and previous studies have demonstrated that cancer cells predominantly acquire lipids through the de novo fatty acid synthesis pathway (Baron et al, 2004). Activation of this pathway is believed to be necessary for carcinogenesis (Zhou et al, 2007).…”
Section: Alteration Of Lipid Metabolism In Cancer Cellsmentioning
confidence: 99%